(untitled) (Bioscience Journal, 2022)
Other herbicides, alone or in combination with glyphosate, may be effective in controlling Richardia brasiliensis, Commelina benghalensis, Conyza sumatrensis e Digitaria insularis. Therefore, the aim of this study was to evaluate the efficacy of herbicides, alone or in combination, in the control of these weeds in the off-season. Three composite experiments were conducted by applying herbicides, alone or in combinations. Experiments 1 and 2 were conducted in Palotina, State of Paraná (PR), Brazil. Experiment 3 in Iporã, PR, Brazil. The three during fall 2017 in fallow areas after soybean harvest. The experiment was a randomized complete block design with 4 replications and weed control at 7, 14, 21, 28, 35, and 42 days after application (DAA). The control of R. brasiliensis and C. benghalensis was evaluated in the three experiments, the control of C. sumatrensis, in experiments 1 and 2, while the control of D. insularis was evaluated only in experiment 3. Data were subjected to analysis of variance and F-test (p < 0.05). The treatment means values of experiments 1 and 2 were compared by Tukey’s test (p < 0.05), and the treatment mean values of experiment 3 were grouped by the Scott and Knott test (p < 0.05). Some herbicide combinations were effective in controlling R. brasiliensis, C. benghalensis, in a single or sequential application. Herbicide combinations were effective in controlling C. sumatrensis with sequential application. Herbicide combinations in a single application did not provide satisfactory final control (≥ 80%) for D. insularis.